Efektivitas Media Karangka Terhadap Kemampuan Pemahaman Konsep Mengurutkan Bilangan Pada Siswa SD - Aulia, Nella Marsha; Fadhilah, Wiwit Syafa’atul; Khofifah, Ayu Dewi Nafisatul; Ermawati, Diana (Papanda, 2025)
This study aims to test the effectiveness of using the framework media (number cards) in improving the understanding of ordering numbers in grade II students of SDN 3 Mayong Kidul. The problem in this study is that many students still have difficulty in understanding the basic concept of number order, which is caused by conventional learning methods and the lack of student interest in mathematics. This study uses a quantitative approach with a Pretest-posttest design to 15 students. Data were collected through multiple choice tests before and after using the framework media, then analyzed using the Normality Test, Paired T Test and N-Gain Test with the help of IBM SPSS Software. The results of this study showed a significant increase in the results of the study on student learning outcomes, with an average posttest score of 82.13, higher than the pretest average of 55.86. The Paired T Test showed a significance value (2-tailed) of 0.000 (<0.05), which means that the use of framework media is effective in improving students' understanding of ordering numbers. The N-Gain test shows an average value of 0.6258 in the moderate category, which means there is a difference or increase in value before and after using the framework media on understanding how to order numbers. So it can be concluded that the framework media can be an innovative solution to overcome the difficulty of learning mathematics on the material of random number sequences from smallest to largest and vice versa.